PENGARUH PEMBERIAN PENDIDIKAN KESEHATAN BANTUAN HIDUP DASAR (BHD) AWAM MELALUI VIDEO TERHADAP TINGKAT PENGETAHUAN ANAK SEKOLAH MENENGAH ATAS (SMA) DI KOTA PONTIANAK - Suhaimi Suhaimi Fauzan Fauzan; Ibnu Kahtan; Herman Herman (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2021)
Abstract Background : Cardiac arrests are the leading cause of death outside the hospital and in the hospital. Previous research has shown that as many as 70% of out-of-hospital cardiac arrests (OHCAs) occur at home. The outcome of the OHCA was poor, only 10.8% of adult victims with non-traumatic cardiac arrest who had received resuscitation efforts from the emergency medical service (EMS) were able to survive until hospital. In everyday life, it is often found that someone suddenly loses consciousness or finds a victim on the street. To deal with this, what has to be done is to provide Basic Life Support (BLS). The provision of information can be started from the school age so that they can easily practice and share information on handling BLS on lay people with their families. Objective: Seeing the effect of providing basic life support (BLS) health education to the community through videos on the level of knowledge of high school children (SMA) in Pontianak city. Methods: This type of research is quantitative research, using a quasi-experimental research design in the form of pre-test and post-test without control. Audiovisual media is effective in increasing the knowledge and skills of respondents. Several studies have stated that self-directed videos can improve the knowledge, attitudes and skills of cardiopulmonary resuscitation (CPR) in high school students. This research was conducted using the method of providing general BLS health education to high school students in Pontianak City. Result: After measuring using a questionnaire, the results of the Wilcoxon test showed a difference in knowledge between pre-test and post-test with a p-value of 0.000 (p<0.05). Conclusion: There was a significant influence on the provision of basic life support (BLS) health education for lay people through video on the level of knowledge of high school children in Pontianak City. Keywords: Basic life support, health education, video, level of knowledge.